Conhecimento local sobre aves, com ênfase em Psittacidae, nos distritos rurais de Cruzeiro dos Peixotos, Martinésia e Tapuirama (Uberlândia-MG) - Saiki, Patrícia Thieme Onofri (2008)
Studies in Ethnobiology recognize the local populations as carriers of great wisdom about the dynamics and functioning of nature. Understand the local knowledge about the environment and its influence on the behavior of the societies is the starting point for the success of conservation strategies, also in places already highly modified by human, as the region of Uberlândia-MG. Ethnoornitology field is still little explored in Brazil and researchs in such area are incipient in the Triângulo Mineiro region. This research investigated the local knowledge of the inhabitants of the rural districts of Cruzeiro dos Peixotos, Martinésia and Tapuirama (Uberlândia-MG) on the ecology, behavior, taxonomy, nomenclature and economic-cultural aspects of the birds of the region, emphasizing the Ethnoecology and Ethnotaxonomy of the Psittacidae of occurrence in the study areas, pointing the agreement and disagreements between the scientific knowledge and the local knowledge. To achieve this aim, it was used instruments for collecting data frequently employed in ethnographic research, such as semi-structured interviews and presentation of audiovisual materials. Ten informants in each district had been interviewed, living at least 10 years in the place, without formal instruction on birds. As results of the research were raised 156 bird species, distributed in 22 orders and 40 families, according to the scientific classification, cited under 245 common names. Most birds cited (n = 97) was identified at the terminal taxon of the scientific classification, being generic the most important category for the local taxonomy. Bird identification and classification by informants followed morphological parameters, such as color, size and vocalization. It was pointed out by informants that the best times to see and hear birds is the dawn and evening, mainly in the "bush" and in backyards. Amazona aestiva, Ara ararauna, Aratinga aurea, Aratinga leucophtalma, Brotogeris chiriri and Forpus xanthopterygius were the Psittacidae species most cited at all stages of the work, and there was an increase in the percentage of citations after presentation of the plates. These species most remembered and recognized by informants also had their vocalizations more easily identified, although the acoustic identification has not been as accurate as the visual identification, due to the great similarity of the vocalization of Psittacidae. Damages in crop and electrical wiring were cited as problems for human. Psittacidae traffic is known by informants, who are aware of the illegality of that trade, suggesting captivity creation through record of the bird in IBAMA. Interviewees informations about breeding and nesting of Psittacidae are similar to the data from scientific literature. They identified the localization of the nests ranging between Psittacidae and spoke of parental care by both parents, which are differentiated by them from small differences in color and size, although doesn t have related in the literature evident sexual dimorphism in the group. The research enabled to known common names not described in the literature. It provided yet indicators of changes in the traditions of the districts inhabitants, due to the reduction of the cultural transmission of the local ecological knowledge, produced and accumulated over the generations. It was perceived that involve local populations in ethnobiological researchs stimulates a rediscovery of the environment around them, which favors the practice of conservation actions and provides rescue of cultural knowledge.